2012
DOI: 10.1093/ehjci/jes274
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of strain and strain rate by two-dimensional speckle tracking in mice: comparison with tissue Doppler echocardiography and conductance catheter measurements

Abstract: In mice, the STI- and TDI-derived strain and strain rate deformation parameters relate closely to intrinsic myocardial function. At low heart rate-to-frame rate ratios (HR/FR), both STI and TDI are equally acceptable for assessing the LV function non-invasively in these animals. At HR/FR (e.g. dobutamine challenge), however, these methods cannot be used interchangeably as STI underestimates S and SR at high values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…Strain values, on the other hand, are still considered adequate at lower frequencies. 27,28 Lower FRs could also have an influence on the feasibility, although this was not different in the current series than in previous reports. 29 Furthermore, although deformation analysis was performed on DICOM images using vendor-independent software, Koopman et al previously showed good correlation with vendor-specific software used for longitudinal strain analysis.…”
Section: <00001contrasting
confidence: 76%
“…Strain values, on the other hand, are still considered adequate at lower frequencies. 27,28 Lower FRs could also have an influence on the feasibility, although this was not different in the current series than in previous reports. 29 Furthermore, although deformation analysis was performed on DICOM images using vendor-independent software, Koopman et al previously showed good correlation with vendor-specific software used for longitudinal strain analysis.…”
Section: <00001contrasting
confidence: 76%
“…[13][14][15] Furthermore, there are limited data on the effect of loading conditions on 2D strain and SR. To date, the only accepted method able to generate load-independent parameters of ventricular function is the conductance catheter method. There have been conflicting results regarding the load sensitivity of the strain and SR of the RV when measured by Doppler 16 and speckle tracking studies.…”
mentioning
confidence: 99%
“…Peak systolic values of radial SR in the anterior and posterior wall were obtained using Tissue Doppler Imaging (TDI) as previously described (Derumeaux et al, 2008). TDI loops were acquired from the same parasternal view with a careful alignment with the radial component of the deformation (Ferferieva et al, 2013) at a mean frame rate of 514 fps and a depth of 1 cm. The Nyquist velocity limit was set at 12 cm/s.…”
Section: Discussionmentioning
confidence: 99%